Relevansi Alasan Pengajuan Isbat Nikah di Pengadilan Agama Majene - Anisa Pratiwi; Sufirman Rahman; Anzar Makkuasa (Journal of Lex Generalis (JLG), 2023)
Tujuan penelitian menganalisis Relevasi alasan Pengajuan Isbat nikah di Pengadilan Agama Majene dan antisipasi penyelundupan hukum dalam perkara legalisasi isbat nikah di Pengadilan Agama Majene. Penelitian ini menggunakan metode penelitian hukum normatif. Hasil penelitian ini menunjukkan bahwa isbat nikah merupakan solusi bagi masyarakat dalam melegalkan perkawianannya yang telah dilaksanakan dengan dibawah tangan ke Pengadilan Agama setempat. Terkait alasan-alasan permohonan isbat nikah yang diajukan para Pemohon di Pengadilan Agama Majene berdasarkan Pasal 7 ayat (3) Kompilasi Hukum Islam diketahui kesimpulan bahwa alasan para Pemohon sebagian masih relevan dan sebagian kurang relevan. The research objective is to analyze the relevance of the reasons for applying for marriage certificates at the Majene Religious Court and to anticipate law smuggling in the legalization of marriage certificates at the Majene Religious Court. This study uses normative legal research methods. The results of this study indicate that marriage consecration is a solution for the community in legalizing their marriage which has been carried out under the hand of the local Religious Court. With regard to the reasons for the application for marriage confirmation submitted by the Petitioners at the Majene Religious Court based on Article 7 paragraph (3) of the Compilation of Islamic Law, it is known that the conclusion is that some of the Petitioners' reasons are still relevant and some are less relevant.